Efficient Na+-storage in a Li4Ti5O12 anode to expand the voltage-window for full SIBs of high energy density. Issue 60 (23rd November 2021) - Li, Chao; Luo, Binhui; Zhao, Youman; Chen, Yongsheng; Yang, Hua; Song, Jingang; Zhao, Lili; Fu, Xiaobo
Abstract : The stable storage of sodium ions always presents some difficulties for sodium-based dual-ion batteries (S-DIBs), such as the irreversibility of guest-storage and kinetic hindrance in the anode. Abstract : The stable storage of sodium ions always presents some difficulties for sodium-based dual-ion batteries (S-DIBs), such as the irreversibility of guest-storage and kinetic hindrance in the anode. Based on the low strain volume and stable phase structure, herein, lithium titanate (LTO, Li4 Ti5 O12 ) was developed to store sodium ions between the working potential (∼0.8 V), which expands the lower plateau over than that of lithium ion storage (∼1.55 V) to obtain a high energy density of full batteries. The spinel lithium titanate shows negligible volume change and extremely stable structure under Na + -storage, which completely overcomes the shortage problems of the Na + -host. Additionally, by the detection of the transfer state of anions and cations in dual-ion batteries, the diffusion coefficient of the sodium ion in the LTO electrode is higher than that of the cathode, which shows that the transport process of sodium ions can meet the kinetic demands of full batteries. Such S-DIBs exhibit a large working voltage of 2.0–4.6 V and stable electrochemical performance over 1280 cycles, which is superior to conventional sodium-based systems, and further exhibit many advantages such as high energy density, environmental friendliness, and low cost.